High Leaf Vein Density Promotes Leaf Gas Exchange by Enhancing Leaf Hydraulic Conductance in Oryza sativa L. Plants - Ye, Miao; Wu, Meng; Zhang, Hao; Zhang, Zuolin; Zhang, Zujian (Frontiers in Plant Science, 2021)
Six cultivated rice genotypes showing different stomatal conductance (gs) values were used to investigate the influence of leaf vein traits on leaf gas exchange and leaf hydraulics. The results showed that gs was the main determinant of the varietal difference in the net photosynthetic rate (PN) while the area-based leaf nitrogen content (Narea) and mesophyll conductance (gm) were not main factors. gs and PN were both positively correlated with leaf hydraulic conductance (Kleaf). A high density of leaf veins (VLA, vein length per leaf area), especially minor leaf veins (VLAminor), was of benefit for improving Kleaf. The proportion of minor leaf vein length to total leaf vein length did not impact the leaf hydraulics or leaf gas exchange. Overall, these findings suggest that a high density of leaf veins, especially minor leaf veins, enhances Kleaf and promotes gs and PN in cultivated rice genotypes and high VLA can be regarded as a high photosynthetic capacity trait in rice plants.